Olefin‐metal π‐interactions of mercury and zinc ions in complexes of neutral quinolylcyclopentadiene derivatives - Enders, Markus; Ludwig, Gunter; Pritzkow, Hans (European journal of inorganic chemistry, 2002)
The donor‐functionalised cyclopentadiene derivative 1 acts as a neutral chelate ligand and forms the zinc and mercury complexes 2 and 3 upon treatment with HgCl2 or ZnCl2. Due to the predefined geometry...